2009
DOI: 10.1088/0953-8984/21/18/185013
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of a novel quasi-2D Cu(II)-trimer system

Abstract: We present structural and magnetic data of a new Cu(2+)(S = 1/2)-containing magnetic trimer system 2b·3CuCl(2)·2H(2)O (b = betaine, C(5)H(11)NO(2)). The trimers form a quasi-2D quantum spin system with an unusual intra-layer exchange coupling topology, which, in principle, supports diagonal four-spin exchange. To describe the magnetic properties, a 2D effective interacting-trimer model has been developed including an intra-trimer coupling J and two inter-trimer couplings J(a) and J(b). The low-energy descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…18) From the crystal structure, it was discussed that (C 5 H 11 -NO 2 ) 2Á 3CuCl 2Á 2H 2 O can be regarded as a quasi twodimensional spin trimer system, where the spin trimer is formed by three Cu 2þ ions with S ¼ 1=2 spin with strong intratrimer exchange interactions. 19) It was also reported that there was no signature of a long-ranger magnetic order down to 2 K. 19) However, the recent detailed measurements of the specific head at low temperatures by Sanda et al revealed that (C 5 H 11 NO 2 ) 2Á 3CuCl 2Á 2H 2 O exhibits a long-range ordering at T N ¼ 1:38 K. 20) It indicates that this compound should be treated as a three-dimensional system with weak interlayer interactions.…”
Section: Experimental Findings In the Typical Trimer Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…18) From the crystal structure, it was discussed that (C 5 H 11 -NO 2 ) 2Á 3CuCl 2Á 2H 2 O can be regarded as a quasi twodimensional spin trimer system, where the spin trimer is formed by three Cu 2þ ions with S ¼ 1=2 spin with strong intratrimer exchange interactions. 19) It was also reported that there was no signature of a long-ranger magnetic order down to 2 K. 19) However, the recent detailed measurements of the specific head at low temperatures by Sanda et al revealed that (C 5 H 11 NO 2 ) 2Á 3CuCl 2Á 2H 2 O exhibits a long-range ordering at T N ¼ 1:38 K. 20) It indicates that this compound should be treated as a three-dimensional system with weak interlayer interactions.…”
Section: Experimental Findings In the Typical Trimer Systemmentioning
confidence: 99%
“…(3.6)] as a y i0 a i0 ¼ 1 À 18,19) (a) Spin trimer configuration on the c ¼ 0 layer. The square represents the unit cell.…”
Section: Magnetic Excitationmentioning
confidence: 99%
See 3 more Smart Citations